Study on the extended steel plate connection for steel slit shear walls. (December 2020) - He, Liusheng; Khadka, Binod
Abstract: The steel slit shear wall (SSSW), made by cutting slits in a steel plate and usually installed between floor beams, is an effective lateral-force-resisting system. To ensure sufficient development of plasticity at the slit ends for seismic energy dissipation, a stiff connection between the floor beam and SSSW is needed to concentrate the story lateral deformation into the SSSW. The present study aims to develop a new connection method using the extended steel plate with the same thickness as the SSSW. To get the optimal design of the extended steel plate, theoretical analysis was conducted first, followed by experimental validation. Two pairs of specimens, with the width-depth ratio of the extended steel plate and with or without out-of-plane constraint being the major parameters, were designed and tested under cyclic loading. Test results showed that out-of-plane constraint worked well in preventing early buckling of the extended steel plate and without using out-of-plane constraint the width-depth ratio of the extended steel plate controlled its overall behavior. Without using the out-of-plane constraint, the extended steel plate with a larger width-depth ratio resulted in its dominant in-plane shear deformation. Adoption of a width-depth ratio of 1.45 of the extended steel plate successfully concentrated over 85% of the inter-story shear deformation into the SSSW, while the extended steel plate with the width-depth ratio of 0.78 exhibited obvious out-of-plane buckling. The extended steel plate with a minimum width-depth ratio of 1.5 is suggested as a convenient and economic method for connecting the SSSW to the floor beams. Finally, a design procedure is given for the proposed SSSW system.